Letter (copy) : Imprisonment of Senor Bratos - Citrine, Walter, 1887-1983
012a-0090-001 Secretary's WMC/FEM/MT/863 3rd May, 1938. The Rt.Hon. Viscount Halifax, K.G., G.C.S.I., Secretary of State for Foreign Affairs, Foreign Office, WHITEHALL, S.W.1. Dear Lord Halifax, IMPRISONMENT OF SENOR BRATOS. Thank you very much for your letter of the 2nd May, regarding Senor Bratos, the Spanish Trade Union leader who has been condemned to death in the prison Los Esculapios at Bilbao. We very much appreciate the action you have taken on his behalf and shall be glad to have any information about him which may reach you. Yours sincerely, General Secretary. 292/946/12a/90